Comparison of SARS‐CoV‐2 detection with the Cobas® 6800/8800 system on gargle samples using two sample processing methods with combined oropharyngeal/nasopharyngeal swab. Issue 12 (5th August 2021) - Benoit, Patrick; Labbé, Annie‐Claude; Lalancette, Linda; Gagnon, Simon; Bonneau, Eric; Lavallée, Christian; Roger, Michel; Fafard, Judith; Dumaresq, Jeannot; Beauchemin, Stéphanie; Coutlée, François
Abstract: Background: Gargle samples have been proposed as a noninvasive method for detection of SARS‐CoV‐2 RNA. The clinical performance of gargle specimens diluted in Cobas® PCR Media and in Cobas® Omni Lysis Reagent was compared to oropharyngeal/nasopharyngeal swab (ONPS) for the detection of SARS‐CoV‐2 RNA. Study Design: Participants were recruited prospectively in two COVID‐19 screening clinics. In addition to the ONPS, participants gargled with 5 ml of natural spring water split in the laboratory as follows: 1 ml was added to 4.3 ml of polymerase chain reaction (PCR) media and 400 μl was added to 200 μl of lysis buffer. Testing was performed with the Cobas® SARS‐CoV‐2 test on the Cobas® 6800 or 8800 platforms. Results: Overall, 134/647 (20.7%) participants were considered infected because the ONPS or at least one gargle test was positive. ONPS had, respectively, a sensitivity of 96.3% (95% confidence interval [CI]: 91.3–98.5); both gargle processing methods were slightly less but equally sensitive (90.3% [95% CI: 83.9–94.3]). When ONPS and gargle specimens were both positive, the mean cycle threshold ( C t ) was significantly higher for gargles, suggesting lower viral loads. Conclusion: Gargle specimens directly added in PCR Media provide a similar clinical sensitivity to chemical lysis, both having a slightly, not significantly, lower sensitivity to ONPS.